Investigation of interactional phenomena and multi wave solutions of the quantum hydrodynamic Zakharov–Kuznetsov model - El-Rashidy Khaled (De Gruyter, 2021)
The symbolic computation with the ansatz function and the logarithmic transformation method are used to obtain a formula for certain exact solutions of the (3+1)\left(3+1) Zakharov–Kuznetsov (Z–K) equation. We use homoclinic breather, three waves method, and double exponential. There is a conflict of results with considerably known results, which indicates the solutions found in this study are new. By selecting appropriate parameter values, 3d representations are plotted to establish W-shaped, multi-peak, and kinky breathers solutions.